Asynchrony of taxonomic, functional and phylogenetic diversity in birds. Issue 7 (25th April 2014) - Monnet, Anne‐Christine; Jiguet, Frédéric; Meynard, Christine N.; Mouillot, David; Mouquet, Nicolas; Thuiller, Wilfried; Devictor, Vincent
Abstract Aim We assessed the temporal trends of taxonomic, functional and phylogenetic diversities in the French avifauna over the last two decades. Additionally, we investigated whether and how this multifaceted approach to biodiversity dynamics can reveal an increasing similarity of local assemblages in terms of species, traits and/or lineages. Location France. Methods We analysed a large‐scale dataset that recorded annual changes in the abundance of 116 breeding birds in France between 1989 and 2012. We decomposed and analysed the spatio‐temporal dynamics of taxonomic, phylogenetic and functional diversities and each of their α‐, β‐ and γ‐components. We also calculated the trend in the mean specialization of bird communities to track the relative success of specialist versus generalist species within communities during the same period. Results We found large variation within and among the temporal trends of each biodiversity facet. On average, we found a marked increase in species and phylogenetic diversity over the period considered, but no particular trend was found for functional diversity. Conversely, changes in β‐diversities for the three facets were characterized by independent and nonlinear trends. We also found a general increase in the local occurrence and abundance of generalist species within local communities. Main conclusions These results highlight a relative asynchrony of the different biodiversity facets occurring at large spatial scales. We show why a multifaceted approach to biodiversity dynamics is needed to better describe and understand changes in community composition in macroecology and conservation biogeography.